A Meta-Analysis Of Request And Apology Speech Acts In L2 Language Learning Of Arab Postgraduate Students At Malaysian Universities (Journal of Human Sciences, 2023)
The speech Acts of Arab students have also been an interesting domain of research due to the translation of phrases by the students to the English language directly from the Arabic language. Currently, various researches have been conducted in this domain. The speech acts of requests are complaint, complement, compliment, greeting, invitation, refusal, request etc. The most commonly used among these requests and apologies which when compared to the rest of them holds a number of repetitions.   This study undertakes a meta-analysis to examine the utilization of request and apology speech acts with respect to native Arab-speaking post-graduate students who communicate with their instructors in the English language. Previous studies were selected with respect to the apology and request speech acts. The studies reveal that the structural formation of the EFL Learners of the English language is like those of the native Arab speakers. It is vital for the EFL learners of Arab countries to understand the difference between standard cultural norms and practices that must be used in English-speaking social settings to avoid a pragmatic miscommunication or in other words failure of the same and hence emphasize linguistic pragmatics for the learners to get accustomed to a cultural environment of English-speaking ones which eventually envisions a communication with clarity and unambiguity.